Développer l’autonomie pour faire face aux vulnérabilités ? Le cas de l’accompagnement au Conseil en Evolution Professionnelle à Pôle Emploi - Maria Pagoni; Stéphanie Fischer (Éducation et Socialisation)
Since the law of March 2014 (concerning lifelong learning and employment), the Professional Development Consulting (abbreviated by CEP) is supposed to transform the accompaniment of professional careers (DGEFP, 2015, 2017), by giving an important place to autonomy and by establishing an alliance between consultants and recipients. In this context, this article aims at questioning the relationship between autonomy and vulnerability in the support developed by the counselors of the CEP. Based on a typology of 14 stories of professional situations told by “Pôle Emploi” (national employment office) counselors, we will try to answer the following questions: what types of vulnerabilities are identified by counselors among the public welcomed at Pôle Emploi? What kind of support is developed in order to increase agency and autonomy and thus reduce vulnerability?